Escherichia coli DNA polymerase I can disrupt G‐quadruplex structures during DNA replication. (8th November 2017) - Teng, Fang‐Yuan; Hou, Xi‐Miao; Fan, San‐Hong; Rety, Stephane; Dou, Shuo‐Xing; Xi, Xu‐Guang
Abstract : Non‐canonical four‐stranded G‐quadruplex (G4) DNA structures can form in G‐rich sequences that are widely distributed throughout the genome. The presence of G4 structures can impair DNA replication by hindering the progress of replicative polymerases (Pols), and failure to resolve these structures can lead to genetic instability. In the present study, we combined different approaches to address the question of whether and how Escherichia coli Pol I resolves G4 obstacles during DNA replication and/or repair. We found that E. coli Pol I‐catalyzed DNA synthesis could be arrested by G4 structures at low protein concentrations and the degree of inhibition was strongly dependent on the stability of the G4 structures. Interestingly, at high protein concentrations, E. coli Pol I was able to overcome some kinds of G4 obstacles without the involvement of other molecules and could achieve complete replication of G4 DNA. Mechanistic studies suggested that multiple Pol I proteins might be implicated in G4 unfolding, and the disruption of G4 structures requires energy derived from dNTP hydrolysis. The present work not only reveals an unrealized function of E. coli Pol I, but also presents a possible mechanism by which G4 structures can be resolved during DNA replication and/or repair in E. coli . Abstract : Escherichia coli polymerase I (Pol I) can be arrested by G‐quadruplex (G4) and the degree of inhibition is dependent on G4 stability. At higher protein concentration, Pol I can completely overcome some kinds of G4 obstacles without the assistance of other proteins. The mechanistic study suggested multiple Pol I proteins may be implicated in G4 unfolding, and disruption of G4 needs the energy derived from dNTPs hydrolysis.